Molecular Phylogenetic Classification of Streptomycetes Isolated from the Rhizosphere of Tropical Legume (Paraserianthes falcataria) (L.) Nielsen - LANGKAH SEMBIRING (Bogor Agricultural University, Indonesia, 2009)
Intrageneric diversity of 556 streptomycetes isolated from the rhizosphere of tropical legume was determined by using molecular taxonomic method based on 16S rDNA. A total of 46 isolates were taken to represent 37 colour groups of the isolates. 16S rDNA were amplified and subsequently sequenced and the sequences data were aligned with streptomycete sequences retrieved from the ribosomal data base project (RDP) data. Phylogenetic trees were generated by using the PHYLIP software package and the matrix of nucleotide similarity and nucleotide difference were generated by using PHYDIT software. The results confirmed and extended the value of 16S rDNA sequencing in streptomycete systematic. The 16S rDNA sequence data showed that most of the tested colour group representatives formed new centers of taxonomic variation within the genus Streptomyces. The generic assignment of these organisms was underpinned by 16S rDNA sequence data which also suggested that most of the strains represented new centers of taxonomic variation. The taxonomic data indicate that diverse populations of streptomycetes are associated with the roots of tropical legume (P. falcataria). Therefore, the combination of selective isolation and molecular taxonomic procedures used in this study provide a powerful way of uncovering new centers of taxonomic variation within the genus Streptomyces. Key words: molecular phylogenetic, classification, streptomycetes, rhizosphere, Paraserianthes falcatharia